A New Magna Charta Universitatum - Noorda, Sijbolt (International Higher Education, 2021)
Identifying, discussing, and sharing core values is important to any university. Since 1988, the Magna Charta Universitatum serves as a public statement of the fundamental principles of autonomous universities. A fresh expression of core values, principles, and responsibilities was needed in view of worldwide successes as well as challenges: This is the underlying idea of the new statement launched in June 2021.